Promising results after hemi-shoulder arthroplasty using pyrolytic carbon heads in young and middle-aged patients - Tsitlakidis, Stefanos; Doll, Julian; Westhauser, Fabian; Wolf, Matthias; Hetto, Pit; Maier, Michael Wolfgang; Sowa, Boris (Orthopaedics & traumatology, 2021)
Introduction - The objective of this prospective cohort study was the assessment of short-term outcome results of shoulder hemiarthroplasty (HA) using pyrolytic carbon (PC) heads. PC has been introduced as a new material to avoid surgical revision due to glenoid erosion after HA. Glenoid erosion due to the use of metallic heads is known to reduce durability. - Hypothesis - HA using PC heads shows comparable or better radiographic and clinical outcome compared to the conventional HA using metallic heads in the short-term. - Patients and methods - This study was conducted as a single center prospective cohort follow-up study including a total number of 16 consecutive HA with PC heads. Inclusion criteria were indication for HA, an intact rotator cuff, no proximal humeral fractures in patient's history and age>18years. Mean age at the time of arthroplasty was 52.8±10.8years. The mean follow-up was 24.3±8.1months. Baseline and follow-up Numeric Rating Scale (NRS), Constant Scores (CS), Range of Motion (ROM) and radiographs were assessed. - Results - At a mean follow-up of 24.3months the mean CS (p<0.001), mean NRS (p<0.001) and mean ROM (p<0.05) improved statistically significant. Subgroup analysis revealed no differences between subgroups (sex, age, diagnosis, and handedness). Survival rate was high (94.1%). One periprosthetic fracture occurred as the only complication during follow-up. Radiographs showed glenoid erosion in one case and subacromial space reduction in two cases. - Discussion - PC heads in HA show satisfying short-term results at a mean follow-up of two years, which are comparable to those of conventional HA. The clinical improvements were highly significant with good implant survival. However, long-term follow-up results are necessary, especially compared to conventional HA. - Level of evidence - IV; observational therapeutic cohort study.